Key stakeholder perspectives on expert-by-experience involvement in the values-based recruitment of student mental health nurses: A co-produced qualitative study. (November 2022) - Watson, Fiona A.; Glascott, Michelle; Eke, Alarna; Hedgecock, Lynda; Kelly, Michael M.; Saint, Phil; Singh, Jack; Small, Victoria; Tasker, Fiona; Walker, Georgia
Abstract: Background: Values-based recruitment is a mandatory process for nursing programmes within UK higher education, with the Nursing Midwifery Council expecting that experts-by-experience are engaged in these recruitment and selection processes. The wider involvement of experts-by-experience in healthcare education is gaining momentum internationally with calls for engagement in all aspects of design and delivery; however, the impact of such involvement in recruitment of nursing students has received little attention, particularly in mental health nursing. Aim: To understand the impact of expert-by-experience involvement in the values-based recruitment of mental health nursing students from the perspective of candidates, experts-by-experience, and academic staff. Design and methods: This qualitative approach was co-designed and implemented by a research team comprised of academics, experts-by-experience, and student mental health nurses. Focus groups and an on-line survey were used to collect data, with Burnard's thematic analysis providing a framework for data analysis. Setting/participants: This study took place at one UK university. Participants included nurse academics, experts-by-experience, and student nurses with experience of a values-based recruitment process. Results: Thematic analysis identified four themes: starting out, collaboration, rich assessment, and stakeholder gains. Whilst not without its challenges, the involvement of experts-by-experience in the recruitment of mental health nursing students was identified as delivering a robust recruitment process, encompassing academic abilities alongside the personal qualities required to make a 'good nurse'. Personal benefits for experts-by-experience, candidates, and academics were also reported. Conclusion: This study provides insights into the impact of experts-by-experience in supporting values-based recruitment. The approach is identified as enhancing the selection process by drawing from academic and lived experience perspectives and highlights to potential candidates, at the outset of their career, the value of meaningful engagement. These findings support the Nursing Midwifery Council's position that experts-by-experience should be engaged in the recruitment and selection of student nurses. Highlights: Expert-by-experience involvement in the recruitment of mental health nursing students Co-produced research by academics, experts-by-experience and student nurses Involvement of experts-by-experience enriches the values-based recruitment process. Involvement brings benefits to experts-by-experience, candidates and academics.